With a little help from my friends: Developing an assisted automated peritoneal dialysis program in Western Australia - Fortnum, D.; Chakera, Aron; Hawkins, N.; Vandepeer, G. (2017)
Background: Nurse-assisted automated peritoneal dialysis (AAPD) offers a model of care that has been successfully used in frail dialysis populations internationally. AAPD offers cost savings over hospitalisation on peritoneal dialysis (PD) or in-centre haemodialysis (HD). Method: A pilot AAPD model of care was developed in Western Australia (WA). Patient evaluation was measured utilising a perceptions of dialysis survey, clinical events, hospitalisation and peritonitis rates, Charlson Comorbidity Index (CCI), KDQoL-SF 36 and a survey. Staff opinions and perceived competency were measured by an online survey. Economic analysis was undertaken. Results: A successful collaborative model was developed. 40 staff were trained and competency significantly improved during program delivery (p < 0.0001). 15 patients with an average CCI score of 8.7 used the service for 18 periods of care over 18 months (mean 33 days SD 47). Two non-renal cause deaths and two episodes of peritonitis occurred. Patient opinions were extremely positive. Cost savings were estimated at $620,000. Conclusion: In WA, an AAPD pilot program has been successfully developed and delivered. A sustainable model has overcome initial hurdles. Staff have gained new skills and delivered effective care, demonstrated by high patient acceptance. The program was cost-effective compared to staying in hospital or transferring to HD.